From Cost to Opportunity: The Role of ESG In Banking - Dan Costin Nițescu; Radu Ciobanu; Adina Elena Călin; Ana-Gabriela Rusu; Eugen-Marian Vierescu (Amfiteatru Economic)
The multifaceted transformations related to ESG have received many labels, and, in this context, each country has chosen words and actions carefully so as to reflect their strategic interests. But from a financial perspective, ESG should answer the strategic question: is it profitable or not? Integration of ESG in banking requires additional investments, digital transformation, and innovation so as to enhance the sector’s role in achieving sustainability goals. This paper aims to give a new perspective on the profitability related questions linked to ESG implementation. Using panel regression techniques on a sample of 98 banks with global reach and aggregated assets of more than 100 trillion dollars from the major financial centres of the world, we inspect whether ESG disclosure and its individual pillars have an impact on the financial performance of banking organisations. The results reflect that, at a holistic level, ESG tends to negatively influencing banks` financial performance, but considering a detailed view on each of its pillars, the results provide encouraging perspectives for all stakeholders and also lessons to be applied both top-down and bottomup by banking organisations. The article provides a comprehensive understanding of the implications for ESG profitability in the banking sector and emphasises the elements to be considered in finding the balance between cost and opportunity.